STRATEGI KOMUNIKASI DALAM KESANTUNAN BERBAHASA KOMUNITAS ANTARSANTRI PONDOK PESANTREN AL-HIKMAH SUKOHARJO - Ferdian Achsani; Elen Inderasari; Hilmy Mahya Masyhuda (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2018)
Communication is one of the most important aspects of human life. Communication strategies are important to facilitate the achievement of the objectives and purpose of language speech. The use of language becomes the most important tool in communication must pay attention to the rules of language politeness. The purpose of this study is to describe various communication strategies in the form of language politeness that occur in the Islamic boarding school community. This research method uses qualitative method because the data is descriptive. Researchers plunged into the field to observe, researchers were students from the Al-Hikmah Islamic boarding school. In collecting data, the researcher uses the technique to see, involve, be competent, record, and record. There are three types of methods in the research stage, namely (1) data collection methods, (2) data analysis methods, and (3) methods for presenting the results of data analysis. Data analysis techniques in this study were carried out in a descriptive qualitative manner with the following steps: (1) collecting verbal data in the form of conversation or dialogue and nonverbal data; (2) record, collect, and select data that has been collected; (3) transcribe data that has been collected; (4) translating findings in regional languages; (5) perform the description and data analysis, and (6) summarize the results of the analysis. Communication strategy in community- language politeness among students of Al-Hikmah Sukoharjo Islamic Boarding School is not influenced by cultural differences. Cultural culture is not one of the factors causing irregularities in the principle of politeness. there is a politeness in which contains the maxim of wisdom, maxim of generosity, maxim of appreciation, maxim of appreciation, maxim of greed, maxim of agreement, and maxim of sympathy in communication speech acts. This happens because they respect each other's cultural culture, both the culture of East Java culture and the culture of Central Java.